Sinkretisme Islam Dalam Tradisi Bele Kampong Kepulauan Riau Perspektif Teologi Lokal Kontekstual - Devina Novela; Syafwan Rozi (Universitas Negeri Padang, 2026)
This study is motivated by the religious reality of the Malay community in the Riau Islands, which is intertwined with local traditions particularly the Bele Kampong tradition that are often viewed as conflicting with Islamic teachings. The study aims to analyze the ritual practices, local theological values, and forms of Islamic syncretism within this tradition. This is a field study employing a descriptive qualitative approach and ethnographic methods. Data were collected through participant observation, in-depth interviews, and documentation involving traditional leaders, religious figures, and the community of Lubuk Village. The findings reveal that the Bele Kampong ritual comprises pre-ritual, ritual, and post-ritual phases, all rich in religious significance. This tradition encompasses values of cosmogony, mythology, ritual, symbolism, concepts of nature, as well as ethics and morality. The syncretism observed represents a contextualization of Islamic values within local culture that strengthens the social and spiritual harmony of the community. This study affirms that the integration of custom and religion constitutes a form of contextual Islam that is relevant for further examination. Keywords: Islamic Syncretism, Bele Kampong Tradition, Contextual Local Theology, Riau Archipelago Malay Culture, Integration of Custom and Religion